Chimeric Plasmodium falciparum parasites expressing Plasmodium vivax circumsporozoite protein fail to produce salivary gland sporozoites - Marin-Mogollon, C; Van Pul, F; Miyazaki, S; Imai, T; Ramesar, J; Salman, A; Winkel, B; Othman, A; Kroeze, H; Chevalley-Maurel, S; Reyes-Sandoval, A; Roestenberg, M; et al. (BioMed Central, 2018)
Background Rodent malaria parasites where the gene encoding circumsporozoite protein (CSP) has been replaced with csp genes from the human malaria parasites, Plasmodium falciparum or Plasmodium vivax, are used as pre-clinical tools to evaluate CSP vaccines in vivo. These chimeric rodent parasites produce sporozoites in Anopheles stephensi mosquitoes that are capable of infecting rodent and human hepatocytes. The availability of chimeric P. falciparum parasites where the pfcsp gene has been replaced by the pvcsp would open up possibilities to test P. vivax CSP vaccines in small scale clinical trials using controlled human malaria infection studies. Methods Using CRISPR/Cas9 gene editing two chimeric P. falciparum parasites, were generated, where the pfcsp gene has been replaced by either one of the two major pvcsp alleles, VK210 or VK247. In addition, a P. falciparum parasite line that lacks CSP expression was also generated. These parasite lines have been analysed for sporozoite production in An. stephensi mosquitoes. Results The two chimeric Pf-PvCSP lines exhibit normal asexual and sexual blood stage development in vitro and produce sporozoite-containing oocysts in An. stephensi mosquitoes. Expression of the corresponding PvCSP was confirmed in oocyst-derived Pf-PvCSP sporozoites. However, most oocysts degenerate before sporozoite formation and sporozoites were not found in either the mosquito haemocoel or salivary glands. Unlike the chimeric Pf-PvCSP parasites, oocysts of P. falciparum parasites lacking CSP expression do not produce sporozoites. Conclusions Chimeric P. falciparum parasites expressing P. vivax circumsporozoite protein fail to produce salivary gland sporozoites. Combined, these studies show that while PvCSP can partially complement the function of PfCSP, species-specific features of CSP govern full sporozoite maturation and development in the two human malaria parasites.